If it bleeds : new fiction - King, Stephen, 1947- (Scribner, 2020)
"In If it Bleeds, King gives readers four brilliant new stories sure to prove as iconic as their predecessors. Once again, King's remarkable range is on full display. In the title story, reader favorite Holly Gibney (from the Bill Hodges Trilogy and The Outsider) must face her fears and possibly another outsider--this time on her own. In 'Mr. Harrigan's Phone,' an intergenerational friendship has a disturbing afterlife. 'The Life of Chuck' explores, beautifully, how each of us contains multitudes. And in 'Rat,' a struggling writer must contend with the darker side of ambition" -- Front jacket flap.